Managing Conflict: A Practical Guide to Resolution in the Workplace (getAbstract Summary). - , getAbstract (linkedin.com, 2019)
Most companies use outdated approaches to conflict management. Learn how to unlock the benefits of conflict in this audio-only review of David Liddle’s book.